Sobre gnomos y gigantes : los tratados grecorromanos y la igualdad soberana de los Estados como ficción histórico-jurídica - Buis, Emiliano J. (2011)
The present paper begins with a study of the treaties comprising the Peace\nof Westphalia and their true correlation with the development of the modern notion of\nsovereign equality of the States. It is from this initial critical analysis that the paper\nmoves on to the study of relationships amongst states in the Greek and Roman world,\nfocusing mainly on those conventions celebrated before the Christian era and in the\nneed of these civilizations to turn to said instruments to fix predictable rules of conduct.\nThe hypotheses for this paper, in accordance to a vast analysis of the conditions pertaining\nto the ancient world, suggests that whenever States established relations in conditions\nof disproportion of power they needed to resort to a written ?conventional? veil\nof equality before the law to mask the real inequality of power